Creating "Bright, Positive" Selves: Discourses of Self and Emotion in a Japanese Public‐Speaking Course. (June 2016) - Dunn, Cynthia Dickel
Abstract: This article examines emotion pedagogy and technologies of the self in two Japanese settings: public‐speaking classes and business‐etiquette training for new employees. Data were gathered through participant‐observation and selective audio recording in both settings. The emotion pedagogy found in these classes aims at polishing the public presentation of self as akarui "bright" and sekkyokuteki "active." The training focuses less on the interpretation of inner feelings or competence in a psychologized emotion register than on inculcating habits of thought and behavior which allow clients to function affectively and effectively within their social contexts. The study demonstrates how the late‐modern reflexive project of self‐fashioning can be embedded in institutional contexts and carried out through metapragmatically explicit emotion pedagogy focusing on the public presentation of self.